Direct Detection of MiRNAs miR-34a, -145, and -218 with CRISPR/Cas13a-nuclease - Timoshenko, O.S.; Kurbatov, L.K.; Khmeleva, S.A.; Ptitsyn, K.G.; Radko, S.P.; Lisitsa, A.V. (Biomedical Chemistry: Research and Methods, 2023)
Using CRISPR/Cas13a-nuclease we have demonstrated a feasibility of direct detection of three miRNAs, miR-34a, -145, and -218 (their molecular signature is suggested as a diagnostic and prognostic biomarker in cervical cancer),. The detection is based on registration of a cleavage of molecular reporters bearing a fluorophore and a quencher by the complex of CRISPR/Cas13a-nuclease and guide RNA (gRNA) with a spacer of 21-23 nucleotides long. The detection sensitivity varied among miRNAs tested by 10-fold, presumably due to the unwanted intramolecular partial base paring of gRNA. The miRNA detection with Cas13a nuclease strongly depended on the presence of background RNA thus potentially compromising its direct application to complex media in a general case. Further optimization of measurement conditions including probably an additional amplification of the signal generated by collateral activity of Cas13a nuclease is necessary to directly detect miR-34a, -145, and -218 in biological samples.